Detection of microbial contaminants of some locally produced fruit juices, ice creams, and yogurts. - Raja'a Khazl. Ali (College of Pharmacy / Mustansiriyah University, 2013)
The study included (45) samples of fruit juices, ice creams and yogurts which locally produced and available at Baghdad markets including some small markets and booths. The study focused on the detection of microbial contaminants by accounting total number of aerobic bacteria, coliform bacteria, E.coli, S. aureus and Salmonella. Results of microbial tests of (20) randomly collected samples of juices selected from local stores and boxes in Baghdad city area showed contamination and invalidity of these samples for human consumption comparing to Iraqi standards with a failure rate reached to 15 % for total count of bacteria, 10% for coliform. The microbial test (15) samples showed a failure rate of 66.5% for aerobic bacteria (T.C) , 60% for E.coli, 65.6 % for coliform bacteria , 13.3 % for staphylococcus aureus. No sign if Salmonella existence was recorded for all tested samples in compare with Iraqi standards. As for yogurts, the microbial tests of (10) samples showed a failure rate of 30% for coliform, no sign of Salmonella existence was recorded for all tested samples.